2022
DOI: 10.1584/jpestics.d22-049
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of fipronil to an invasive ant, <i>Lepisiota frauenfeldi</i>

Abstract: Slow-acting fipronil is one of the best components for controlling invasive ants. However, its efficacy against invasive Lepisiota frauenfeldi, which recently invaded Japan, remains unclear.Here, its acute toxicity to Le. frauenfeldi was assessed, and its lethal concentrations were compared with those against other invasive ants (Linepithema humile and Solenopsis invicta). The LC 10 and LC 50 values of fipronil for Le. frauenfeldi were significantly lower than the previously reported values for Li. humile and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…1 However, the overuse of FPN leads to environmental pollution from water to soil, causing a range of harmful consequences in fish, aquatic invertebrates, land birds, and consequently humans. [2][3][4][5] Due to its high toxicity, FPN has been forbidden or strictly restricted in many countries. 6,7 However, recent studies demonstrated that FPN contamination is still widespread in surface water and groundwater resources beyond its permissible limitation.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, the overuse of FPN leads to environmental pollution from water to soil, causing a range of harmful consequences in fish, aquatic invertebrates, land birds, and consequently humans. [2][3][4][5] Due to its high toxicity, FPN has been forbidden or strictly restricted in many countries. 6,7 However, recent studies demonstrated that FPN contamination is still widespread in surface water and groundwater resources beyond its permissible limitation.…”
Section: Introductionmentioning
confidence: 99%